1998
DOI: 10.1139/b98-152
|View full text |Cite
|
Sign up to set email alerts
|

Induction of "filamentous structures" in wild type Antirrhinum majus flowers by benzylaminopurine

Abstract: The cytokinin, N 6 -benzylaminopurine (BAP), when applied to young inflorescences of wild-type Antirrhinum majus L., resulted in the formation of chimeric "filamentous structures" in the dorsal region of the third whorl, the position where a stamen primordium is suppressed in wild-type flowers. In addition, BAP induced similar filamentous structures in between the first and second whorls, and this response was concentration dependent. The basal region of the filamentous structures was similar to the filament o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Other studies have shown that application of BAP to developing inflorescences results in changes in floral organ identity and number, explained by extended meristematic activity (Venglat and Sawhney, 1996;Blahut-Beatty et al, 1998;Lindsay et al, 2006). Interestingly, BAP-treated mature flowers and fruits did not produce ectopic tissue (this study), suggesting that cytokinins have a proliferation-inducing activity in young gynoecia only, where the medial tissues show meristematic characteristics.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Other studies have shown that application of BAP to developing inflorescences results in changes in floral organ identity and number, explained by extended meristematic activity (Venglat and Sawhney, 1996;Blahut-Beatty et al, 1998;Lindsay et al, 2006). Interestingly, BAP-treated mature flowers and fruits did not produce ectopic tissue (this study), suggesting that cytokinins have a proliferation-inducing activity in young gynoecia only, where the medial tissues show meristematic characteristics.…”
Section: Discussionsupporting
confidence: 53%
“…Other studies have shown that application of BAP to developing inflorescences results in changes in floral organ identity and number, explained by extended meristematic activity (Venglat and Sawhney, 1996; Blahut‐Beatty et al. , 1998; Lindsay et al.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the effect of the transitory action of 10 mM kinetin on expression of apogamy is concerned (Fig. 8), it is relevant to note that in flowering plants, cell-inheritable changes may result not only from habituation (Meins and Binns, 1979) but also by transitory activation of certain homeotic genes (Blahut-Beatty et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover RNase could depolymerize doublestranded RNA, known to be involved in epigenetic inheritance (Matzke et al, 2001). Treatment with kinetin is known to induce stable epigenetic changes in plants (Meins and Binns, 1979;Blahut-Beatty et al, 1998).…”
Section: Introductionmentioning
confidence: 99%